2019
DOI: 10.1097/nmd.0000000000000957
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Serum Levels of Cortisol and Inflammatory Cytokines in People With Depression

Abstract: This cross-sectional study aimed at measuring the correlation and association between serum levels of cortisol, inflammatory cytokines, and depression and to measure the detection accuracy of serum levels of cortisol in serum samples. In total, 89 male participants were recruited into this study from June 15, 2017, to September 31, 2017. The Hamilton Depression Rating Scale, Beck Anxiety Inventory, and Pittsburgh Sleep Quality Index were used to investigate the mental health status of the participants. Serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 43 publications
2
51
0
1
Order By: Relevance
“…According to the latest research, education level, age, and other factors are also closely related to the occurrence of anxiety (7) found that cancer patients or their family members who were over 60 years of age or working as farmers were more likely to have anxiety, while those who were educated in middle school or above were less likely to have anxiety. In addition, according to some previous studies and relevant guidelines (18,21), poor sleep quality increased the risk of psychological abnormality, which was consistent with the results of this study. The multi-factor analysis in this study also suggested that for cancer patients and their families, the farmer occupation and higher sleep disorder assessment score were independent risk factors for anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…According to the latest research, education level, age, and other factors are also closely related to the occurrence of anxiety (7) found that cancer patients or their family members who were over 60 years of age or working as farmers were more likely to have anxiety, while those who were educated in middle school or above were less likely to have anxiety. In addition, according to some previous studies and relevant guidelines (18,21), poor sleep quality increased the risk of psychological abnormality, which was consistent with the results of this study. The multi-factor analysis in this study also suggested that for cancer patients and their families, the farmer occupation and higher sleep disorder assessment score were independent risk factors for anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…However, some studies that used a mathematical prediction model pointed to serum cortisol as a critical biomarker of MDD diagnosis [ 38 , 39 ]. Nevertheless, it is important to highlight that the sample of those studies did not comprise de novo patients, but participants with distinct MDD severities jointed into a single group [ 38 , 39 ], in contrast to our sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies that used a mathematical prediction model pointed to serum cortisol as a critical biomarker of MDD diagnosis [ 38 , 39 ]. Nevertheless, it is important to highlight that the sample of those studies did not comprise de novo patients, but participants with distinct MDD severities jointed into a single group [ 38 , 39 ], in contrast to our sample. Considering that a MDD diagnosis is more complex for subjects with mild than it is for severely impaired patients, our model contemplates a sample with typical characteristics for a first MDD diagnosis and thus can be especially useful for clinical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that patients in the NG were in a very weak mental state, because they complained of symptoms of LOH despite having a normal T level. Furthermore, gonadotropin was elevated in the CHG to compensate for T. Gonadotropin might cause a decrease in cortisol due to feedback through the hypothalamus 22 . These endocrinological characteristics of the CHG might also induce symptomatic changes in the future, even though T secretion is compensated by high stimulation from LH.…”
Section: Discussionmentioning
confidence: 99%